A descriptive study on customer perception of space efficiency optimizing layouts for carinderia design - Burlaos, Maria Krishna S.; Peñaflor, Lorelie Christine L.; Ilumin, Marx Janeil C.
Carinderias are deeply rooted in Filipino food culture, offering affordable meals in informal, typically home-based settings. While affordability is prioritized, customer perception of space efficiency is often overlooked in their design. This descriptive study aims to understand how customers perceive space efficiency in three selected carinderias in Area 2, UP Diliman, focusing on seating arrangement, food service flow, space clearances, and ventilation. A mix of data collection methods was used, combining observations, interviews with carinderia owners, and surveys from 90 customers (30 per carinderia). The carinderias were selected through purposive sampling, and the survey participants through convenience sampling. The key interior design features differ for each carinderia. The order counter is either at the entrance or in the rear, ventilation is provided by electric fans, seating capacity is between twenty (20) and forty (40), furniture arrangement is either linear or grid, and a serving counter is separate from the order counter in one carinderia. Overall, customers perceive features such as inadequate ventilation, limited accessibility, and tight clearances to be the key space efficiency issues in the carinderias that negatively impact their dining experience, while flexible seating (groups and individual) is a positive feature. For an optimal carinderia layout, it is recommended to have an open-frontage design that maximizes natural ventilation, have canopies for sun protection to reduce thermal discomfort, have entrance-positioned counters to avoid interior congestion, and have a linear pathway from entrance to interior for better mobility and clear flow of movement. This research demonstrates that space efficiency is a user-centered process of designing not just for an intended function but according to how people utilize and experience spaces.